Endoscopic evaluation of acute intestinal graft-versus-host disease after allogeneic hematopoietic cell transplantation - Altun, Reskan; Gökmen, Ayla; Tek, İbrahim; Soydan, Ender; Kurt Yüksel, Meltem (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Acute graft-versus-host disease (GVHD) is a common complication of haematopoietic cell transplantation (HCT), with the gastrointestinal tract (GIT) as one of the main target organs. There is a lack of consensus regarding the site in GIT with the highest sensitivity for biopsy. The present study aimed to determine the endoscopic and histological findings in acute GVHD. Materials and Methods: The data of 111 patients who had received allogeneic HCT were retrospectively reviewed. Results: Allogeneic HCT was performed in 111 patients, of whom 27 (24.3%) had developed acute GVHD. Nineteen of the 111 patients with intestinal symptoms were evaluated for intestinal involvement, and 17 were diagnosed with acute intestinal GVHD. Upper endoscopic findings had a sensitivity of 64.7%, a specificity of 50%, a positive predictive value of 91.6% and a negative predictive value of 14.2%. The diagnostic accuracy of upper endoscopy was 63.1%. Lower endoscopic findings had a sensitivity of 40% and a specificity of 0%. The diagnostic accuracy of upper endoscopy with duodenal biopsy and sigmoidoscopy was 94.1%. Conclusion: Endoscopic findings are nonspecific in acute intestinal GVHD. There is little agreement between endoscopic findings and histopathology; thus, biopsies are essential. In patients with intestinal symptoms after HCT, upper endoscopy with duodenal biopsy and sigmoidoscopy has an acceptable diagnostic yield for intestinal involvement.